Strategic Foresight analysis of droughts in southern Africa and implications for food security - Gbegbelegbe, S.; Chikoye, D.; Alene, A.; Kyei-Boahen, S.; Chigeza, G. (Frontiers Media, 2024)
Southern Africa has been experiencing long-term changes in its climate and future projections imply that droughts should last longer and become more intense in southern Africa. Already, the region has been experiencing an increase in consecutive drought years. This study contributes to the literature by using bio-economic modeling to simulate the impact of future droughts on food security in southern Africa and identify plausible pathways for enhancing regional food security under drought. Food production and food security in southern Africa were projected under drought using an adjusted version of a multi-market and multi-commodity global model, the International Model for the Policy Analysis of Agricultural Commodities and Trade (IMPACT), version 3.2. The results suggest that with moderate economic growth and no drought, southern Africa would not become wealthy enough to mitigate food insecurity by 2040. In this context, recurrent droughts would worsen food security by severely affecting the production of maize, the key staple food in the region. With consecutive two-year regional droughts, like what was experienced in 2014/15 and 2015/16, most countries would experience an increase of at least 10% in the number of people at risk of hunger within a single year. Key measures which could help enhance food security under droughts include (1) breeding for stress-resilient maize (resistance to both heat and drought stresses); (2) promote crop and diet diversification, especially in countries highly dependent on maize as a staple food crop; and (3) invest in rainwater harvesting.